Analisis Kestabilan Lereng Menggunakan Metode Janbu Simplified Pada Blok Bukit Jaya Pt. Cahaya Bumi Perdana Kota Sawahlunto Provinsi Sumatera Barat - Muhammad Ichsan Busra; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. At PT. Cahaya Bumi Perdana, there is a slope with a height of about ± 30 m with a slope of 710 on the slope there are two types of slope-forming material that are in 1 bench, namely soil and rock material that is likely to occur landslides, with the slope conditions potentially endangering workers and hindering production. Based on the data from the physical and mechanical properties of sandstone rock, the original bulk density value was 8.024 KN / m3, the saturated weight value was 16.016 KN / m3, the dry weight value was 5.005 KN / m3, cohesion (c) = 0.0059 Mpa and the inner angle of shear. (ϕ) = 63,808 °. The analysis of the value of the safety factor (FK) and the recommendation of the actual slope geometry used the janbusimplified method with a height of 33m and a slope of 65˚ so that the FK obtained was 1.427. For geometric recommendations for slopes in a saturated state using the Janbu simplified method with a height of 33m and a slope of 65˚, the FK obtained is 1.317. From the value of the safety factor (FK) the recommendations obtained can be concluded that the slopes are stable.Keyword: Physical and Mechanical Properties of Rocks, Slope Geometry, Janbu Simplified, Safety Factors